Islamic Republic of Afghanistan : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
The report describes the policy framework for the Interim Afghanistan National Development Strategy (I-ANDS) and the vision for Afghanistan's developments. It reviews the progress under I-ANDS, analyzes the macroeconomic environment, characteristics of poverty and the policy goals, assesses the national budgeting framework through which the I-ANDS will be integrated into Afghanistan's financial planning mechanisms to ensure both fiscal sustainability and financial independence, and also summarizes how government policies and programs will be transparently monitored, coordinated, refined, and revised in the full ANDS.